THE EFFECT OF TAXPAYER ATTITUDE, TAXPAYER AWARENESS, AND EDUCATION LEVEL ON TAXPAYER COMPLIANCE IN PAYING RURAL AND URBAN LAND AND BUILDING TAXES (UN-P2) (Case Research in Teras District, Boyolali Regency) - Dany Prasetyawati; Desy Nur Pratiwi; Hadi Samanto (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This research aims to analyze the attitude, awareness of taxpayers and level of education towards taxpayer compliance in paying the Rural and Urban Land and Building Tax in Teras District. This type of research is quantitative research with primary data. The research population is the rural and urban land and building taxpayers in Teras District, Boyolali Regency with a total of 50.052. The number of samples is 397 taxpayers obtained by calculating the Slovin formula with an error rate of 5%. The sampling technique used random sampling based on the village. The method of data analysis in this research used the multiple linear regression analysis method using the SPSS test tool. Hypothesis testing using the F test, t test and the coefficient of determination (R2). Based on the results of the research, it can be concluded that the attitude, awareness of taxpayers and level of education affect taxpayer compliance in paying the Rural and Urban Land and Building Tax.